2018
DOI: 10.1111/jace.16013
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physical characteristics of Au2O3‐doped sodium antimonate glasses – Part I

Abstract: Na2O‐Sb2O3 glasses doped with different concentrations of Au2O3 were prepared by melt quenching technique and later were heat treated at 800°C for 6 hours. Structural analysis by XRD, XPS, SEM, EDS, and DSC techniques indicated that the samples are embedded with multiple crystallites composed of Sb3+, Sb5+, Au3+ ions, and Au0 metallic particles. These studies have further demonstrated a gradual increasing fraction of Au0 metallic particles with increasing Au2O3 concentration. IR spectral studies suggested incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Additionally, Ashok et al 19) reported that in sodium antimonite glasses, the gold atom substitutes a part of Sb 3+ in Sb 2 O 3 and exists as Au 3+ . Then, the Au 0 formation process occurs with Sb 2 O 3 as a reducing agent:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Ashok et al 19) reported that in sodium antimonite glasses, the gold atom substitutes a part of Sb 3+ in Sb 2 O 3 and exists as Au 3+ . Then, the Au 0 formation process occurs with Sb 2 O 3 as a reducing agent:…”
Section: Resultsmentioning
confidence: 99%
“…The red shift of the peak wavelength with the temperature of isothermal treatment is related to the variation in the diameter of gold particles. 16)18) Red colors in the SPG sample probably containing gold nanoparticles with diameters of 515 nm 15), 19) were obtained via isothermal treatments at 600 or 620°C. As for the 10B-SPG sample, the viscosity at 600620°C was expected to be 7.7 © 10 8 9.3 © 10 9 Pa•s via the analysis of the VFT equation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Using the values of density d and average molecular weight M of Li 2 O-Nb 2 O 5 -P 2 O 5 :Ag 2 O glasses, Ag + ion concentration N i and mean Ag + ion separation r i are evaluated using the conventional formulae (mentioned in our recent report [19]) and are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The alkali antimonatate glass‐ceramic containing gold matallic particles are predicted to be more useful as electrolytes in solid‐state batteries, in the design of nano‐dimensional optoelectronic circuits and optical memory devices with very high recording speed and storage . In continuation of earlier studies and for getting further support of these findings and for having some knowledge over electrical characteristics, this study is aimed to report results of quantitative studies on dielectric properties over broad ranges of continuous frequencies and temperatures, A.C. and D.C. conductivities and other related parameters measured as a function of concentration of Au 2 O 3 . For better assessment of the structural modifications taking place in the material due to the varied concentration of Au 2 O 3 , results of Raman spectra are also used in this study.…”
Section: Introductionmentioning
confidence: 96%
“…The studies have further revealed increasing concentration of Sb 5+ crystal phases and Au 0 metallic particles with a gradual increase in Au 2 O 3 content in the samples. The increasing presence of Sb 5+ ions (that are predicted to participate in the glass network with Sb(v)O 4 structural units) causes to increase the degree of polymerization of the host glass network …”
Section: Introductionmentioning
confidence: 99%